Soldier Readiness: Past to Present, Initial Entry Training (Journal of Leadership, Accountability and Ethics, 2017)
This case study looks at Soldier Readiness through the evolution of Initial Entry Training for United States Army enlisted members. The study was conducted via a semi-structured, open ended qualitative interview of a senior enlisted Army Soldier. Manual coding was used after transcription by way of In Vivo first cycle coding and Focused second cycle coding to discover themes over the last twenty plus years. Changes in culture via technology and world events changed the American society, the Military changed with it.
Keywords: Leadership; Ethics; Soldier Readiness; technology